DNA oxidation profiles of copper phenanthrene chemical nucleases - Molphy, Zara; Slator, Creina; Chatgilialoglu, Chryssostomos; Kellett, Andrew (Frontiers in Chemistry, 2015)
The deleterious effects of metal-catalyzed reactive oxygen species (ROS) in biological systems can be seen in a wide variety of pathological conditions including cancer, cardiovascular disease, aging, and neurodegenerative disorder. On the other hand however, targeted ROS production in the vicinity of nucleic acids—as demonstrated by metal-activated bleomycin—has paved the way for ROS-active chemotherapeutic drug development. Herein we report mechanistic investigations into the oxidative nuclease activity and redox properties of copper(II) developmental therapeutics [Cu(DPQ)(phen)]2+ (Cu-DPQ-Phen), [Cu(DPPZ)(phen)]2+ (Cu-DPPZ-Phen), and [Cu(phen)22(μ-terph)](terph) (Cu-Terph), with results being compared directly to Sigman's reagent [Cu(phen)2]2+ throughout (phen = 1,10-phenanthroline; DPQ = dipyridoquinoxaline; DPPZ = dipyridophenazine; Terph = terephthalate). Oxidative DNA damage was identified at the minor groove through use of surface bound recognition elements of methyl green, netropsin, and [Co(NH3)6]Cl3 that functioned to control complex accessibility at selected regions. ROS-specific scavengers and stabilizers were employed to identify the cleavage process, the results of which infer hydrogen peroxide produced metal-hydroxo or free hydroxyl radicals (•OH) as the predominant species. The extent of DNA damage owing to these radicals was then quantified through 8-oxo-2′-deoxyguanosine (8-oxo-dG) lesion detection under ELISA protocol with the overall trend following Cu-DPQ-Phen > Cu-Terph > Cu-Phen > Cu-DPPZ. Finally, the effects of oxidative damage on DNA replication processes were investigated using the polymerase chain reaction (PCR) where amplification of 120 base pair DNA sequences of varying base content were inhibited—particularly along A-T rich chains—through oxidative damage of template strands.